Fresh-Cut Vegetables Processing: Environmental Sustainability and Food Safety Issues in a Comprehensive Perspective - Raffo, Antonio; Paoletti, Flavio (Frontiers in Sustainable Food Systems, 2022)
The fresh-cut industry supplies the food market with healthy fresh fruit and vegetables and, in that way, may contribute to improve the nutritional status of the general population. On the other hand, over the last few years increasing concerns have been raised regarding the environmental impact of the fresh-cut industry, human health risks from exposure to disinfection by-products found in fresh-cut products and chlorine-based disinfection treatments during produce processing. This review provides a comprehensive view of the main interlinked aspects related to food safety and environmental impact of processing of fresh-cut vegetables. Advantages and downsides of the mainstream disinfection strategy, based on the use of chlorine-related disinfecting agents, along with some alternative treatments close to a wide commercial application, are discussed. Limitation in the application of these strategies to processing of organic fresh-cut produce are also highlighted, examining the specific environmental and food safety problems in the organic sector. Areas where lack of available information hinders at present a clear understanding of priorities of research and action are pointed out. Innovative conceptual tools are proposed to address these multiple and interlinking issues and to overcome limitations of currently available technologies. A comprehensive and multidisciplinary approach is suggested to move toward a more safe and environmentally sustainable production of fresh-cut products.